Low protein intake during reproduction compromises the recovery of lactation‐induced bone loss in female mouse dams without affecting skeletal muscles. Issue 9 (11th July 2020) - Kanakis, Ioannis; Alameddine, Moussira; Scalabrin, Mattia; van 't Hof, Rob J.; Liloglou, Triantafillos; Ozanne, Susan E.; Goljanek‐Whysall, Katarzyna; Vasilaki, Aphrodite
Abstract: Lactation‐induced bone loss occurs due to high calcium requirements for fetal growth but skeletal recovery is normally achieved promptly postweaning. Dietary protein is vital for fetus and mother but the effects of protein undernutrition on the maternal skeleton and skeletal muscles are largely unknown. We used mouse dams fed with normal (N, 20%) or low (L, 8%) protein diet during gestation and lactation and maintained on the same diets (NN, LL) or switched from low to normal (LN) during a 28 d skeletal restoration period post lactation. Skeletal muscle morphology and neuromuscular junction integrity was not different between any of the groups. However, dams fed the low protein diet showed extensive bone loss by the end of lactation, followed by full skeletal recovery in NN dams, partial recovery in LN and poor bone recovery in LL dams. Primary osteoblasts from low protein diet fed mice showed decreased in vitro bone formation and decreased osteogenic marker gene expression; promoter methylation analysis by pyrosequencing showed no differences in Bmpr1a, Ptch1, Sirt1, Osx, and Igf1r osteoregulators, while miR‐26a, ‐34a, and ‐125b expression was found altered in low protein fed mice. Therefore, normal protein diet is indispensable for maternal musculoskeletal health during the reproductive period.